An Evaluation of Nigeria’s Socioeconomic Development and the Impact of Governance Cost on Economic Growth 2019-2024. - Ajiteru,S.A.R; Sulaiman T.H; Abalaka, J.N (International Forum of Researchers and Lecturers, 2025)
The study looked into how Nigeria's democratic system's economic growth was impacted by the cost of governance. The cost of governance factors is divided into general GDP was the dependent variable and a stand-in for economic growth, while administration, defense, internal security, and national assembly were the explanatory variables. The study examined Nigeria's fourth republic's civil rule from 2019 to 2024. Ordinary Least Square regression and diagnostic tests were performed. The findings indicate that while internal security (-106.17 ISEC) has a negative impact on GDP, general administration (8.67 GA), defense (169.99 DEF), and national assembly (496.50 NAS) have favorable effects. According to the hypotheses' summary, (1) the federal government's expenditure on general administrations has no discernible positive impact on Nigeria's economic growth; (2) the federal government's expenditure on defense has a discernible positive impact on Nigeria's economic growth; and (3) the federal government's expenditure on internal Nigeria's economic growth is significantly impacted negatively by security, whereas the country's economic growth is significantly impacted positively by the federal government's national assembly costs. The research suggested, among other things, that the funds allocated to internal security be examined and that cost-benefit studies be performed on the parastatals that receive the funds.